Thrombogenicity studies on micro/nano topographic surfaces - Koh, Li Buay (2010)
Platelet adhesion and activation resulting from the interaction between the flowing blood and the surface of foreign material of a medical device or implant are adverse events that lead to the formation of thrombus. The modulation of platelet-surface interactions to increase the thromboresistance of foreign surfaces is therefore a vital aspect in the design of blood-compatible surfaces. In this thesis, the effects of fibrinogen adsorption and subsequent platelet interaction on a variety of surfaces with chemical and topographical structures are investigated.